2015
DOI: 10.1038/srep11177
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh scatter based order of magnitude increase in distributed temperature and strain sensing by simple UV exposure of optical fibre

Abstract: We present a technique to improve signal strength, and therefore sensitivity in distributed temperature and strain sensing (DTSS) using Frequency domain Rayleigh scatter. A simple UV exposure of a hydrogen loaded standard SMF-28 fibre core is shown to enhance the Rayleigh back-scattered light dramatically by ten-fold, independent of the presence of a Bragg grating, and is therefore created by the UV exposure alone. This increase in Rayleigh back-scatter allows an order-of-magnitude increase in temperature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(90 citation statements)
references
References 22 publications
(22 reference statements)
2
83
0
Order By: Relevance
“…This is mainly due to the presence of dopant inside the fiber core and to the larger numerical aperture (NA) which collects more of the back-scattered light. However, as predicted by Loranger et al [22], UV exposed fibers (Hydrogen-loaded SMF-28 in this case) show a radical increase in the backscattered signal of about ~6300 times (~37dB). Contrary to the previous report on UV-exposed Rayleigh enhancement caused by the creation of color centers (defects) yielding a Rayleigh enhancement of ~20-25 dB [22], the fiber studied here actually had a strong and chirped (~5 nm) FBG written with a Bragg wavelength outside the scanned bandwidth for the distributed sensing.…”
Section: Optimizing Fiber Backscattermentioning
confidence: 74%
See 3 more Smart Citations
“…This is mainly due to the presence of dopant inside the fiber core and to the larger numerical aperture (NA) which collects more of the back-scattered light. However, as predicted by Loranger et al [22], UV exposed fibers (Hydrogen-loaded SMF-28 in this case) show a radical increase in the backscattered signal of about ~6300 times (~37dB). Contrary to the previous report on UV-exposed Rayleigh enhancement caused by the creation of color centers (defects) yielding a Rayleigh enhancement of ~20-25 dB [22], the fiber studied here actually had a strong and chirped (~5 nm) FBG written with a Bragg wavelength outside the scanned bandwidth for the distributed sensing.…”
Section: Optimizing Fiber Backscattermentioning
confidence: 74%
“…However, as predicted by Loranger et al [22], UV exposed fibers (Hydrogen-loaded SMF-28 in this case) show a radical increase in the backscattered signal of about ~6300 times (~37dB). Contrary to the previous report on UV-exposed Rayleigh enhancement caused by the creation of color centers (defects) yielding a Rayleigh enhancement of ~20-25 dB [22], the fiber studied here actually had a strong and chirped (~5 nm) FBG written with a Bragg wavelength outside the scanned bandwidth for the distributed sensing. Scanning the laser close to the spectrum of the FBG allows a much higher signal, but limits the sensing length as the signal is quickly attenuated.…”
Section: Optimizing Fiber Backscattermentioning
confidence: 74%
See 2 more Smart Citations
“…Loranger et al reported a method to enhance the Rayleigh backscattering signal for improved SNR measurement in ϕ-OTDR systems [22]. The system is based on a costeffective method with reduced fabrication complexity based on exposing a single-mode fiber to UV light without requiring critical alignment compare to the writing of multiple FBGs.…”
Section: ϕ-Otdr Sensors For Measuring Change In Backscattering Intensitymentioning
confidence: 99%